Acute enteritis with pelvic SBRT: Influence of bowel delineation methods - Akshay Dinesan; Maneesh Singh; Prachi Mehta; Priyamvada Maitre; Vedang Murthy (Clinical and Translational Radiation Oncology)
Purpose: One fourth of the patients receiving SBRT to prostate and pelvis develop mild to moderate acute enteritis. In this study, we aim to study bowel dosimetry for different methods of bowel delineation in patients with and without acute bowel toxicity after whole-pelvic SBRT (WP-SBRT). Methods and materials: In this prospective study, patients with high-risk prostate cancer treated with WP-SBRT were identified. Patients with acute bowel toxicity (CTCAE v5.0) were included as cases while those without were controls. All the patients had previously received 35–36.25 Gy in 5 fractions to the prostate and 25 Gy in 5 fractions to the pelvis. The bowel was contoured on the planning CT scan using seven different methods, namely- bowel bag (BB), small bowel loop (SB), large bowel loop (LB), combined bowel loop (BL) and bowel loops with margins (BL + 0.5 cm, BL + 1 cm and BL + 1.5 cm). The original clinically used plan was applied to all the contouring methods and dose-volume parameters studied. Results: A total of 102 patients treated with WP-SBRT were screened and only those with properly documented acute toxicity were included for further analysis. While none of the patients had grade 3 bowel toxicity, 23 (22.5 %) patients had grade 1–2 acute enteritis, and 23 patients without were selected as cases and controls respectively. On visual assessment, the composite dose volume histogram (DVH) were similar for cases and controls for all the delineation methods studied. Objectively, the volume of the bowel structures receiving 7 Gy, 14 Gy, and 25 Gy did not show any statistically significant difference between cases and controls. One in five patients treated with WP-SBRT using bowel bag dose constraints of V7 < 1500 cc, V14 < 500 cc and V25 < 50 cc had acute enteritis. Conclusion: There was no significant difference in planned bowel doses for different bowel delineation methods in patients with prostate cancer treated with WP-SBRT with or without acute bowel toxicity.